Appropriate Sets of Criteria for Innovation Adoption of IS Security in Organizations - Sandy Kosasi; Vedyanto Vedyanto; I Dewa Ayu Eka Yuliani (IAES Indonesia Section, 2018)
Determining sets of criteria and alternatives becoming main priorities is essential to guarantee the success of innovation adoption of Information System (IS) security. The goal of this research was to select and determine important entities as representation of each criterion for managers in making decisions of innovation adoption of IS security. This research applied Technology-Organization-Environment (TOE) Framework, and Human-Organization-Technology-Fit (HOT-Fit) Model to map relative importance variables of criteria and alternatives. AHP Approach was applied for computation simulation to determine priorities of criteria and alternatives. Results show that a principal criterion is manpower of organizations. The eigen factor score is 4.398. Moreover, alternatives covering complexity, financial resources, intensity of competition, and CIO innovativeness have these respective eigen factors scores: 4.326, 9.307, 4.376, and 4.545.